Maximal Strength, Muscular Endurance and Inflammatory Biomarkers in Young Adult Men - Vaara, J. P.; Vasankari, T.; Fogelholm, M.; Häkkinen, K.; Santtila, M.; Kyröläinen, H. (International Journal of Sports Medicine, 2014)
The aim was to study associations of maximal strength and muscular endurance with inflammatory biomarkers independent of cardiorespiratory fitness in those with and without abdominal obesity. 686 young healthy men participated (25±5 years). Maximal strength was measured via isometric testing using dynamometers to determine maximal strength index. Muscular endurance index consisted of push-ups, sit-ups and repeated squats. An indirect cycle ergometer test until exhaustion was used to estimate maximal aerobic capacity (VO2max). Participants were stratified according to those with (>102 cm) and those without abdominal obesity (<102 cm) based on waist circumference. Inflammatory factors (C-reactive protein, interleukin-6 and tumour necrosis factor alpha) were analysed from serum samples. Maximal strength and muscular endurance were inversely associated with IL-6 in those with (β=−0.49, −0.39, respectively) (p<0.05) and in those without abdominal obesity (β=−0.08, −0.14, respectively) (p<0.05) adjusted for smoking and cardiorespiratory fitness. After adjusting for smoking and cardiorespiratory fitness, maximal strength and muscular endurance were inversely associated with CRP only in those without abdominal obesity (β=−0.11, −0.26, respectively) (p<0.05). This cross-sectional study demonstrated that muscular fitness is inversely associated with C-reactive protein and IL-6 concentrations in young adult men independent of cardiorespiratory fitness.
Keywords: muscle fitness; maximal strength; inflammation; C-reactive protein; tumor necrosis factor alpha; interleukin-6